Influence of Merchandising on Customer Purchasing Behavior in Superstores of Kathmandu Valley - Khadka, Ajaya Kumar; Rai, Bharat; Khadka, Srijana (KMC Research Journal, 2023)
This research examines the influence and relationship of product merchandising elements with consumer buying behavior within superstores. The study investigates five key independent variables: design feature, ambiance, product assortment, brand image, and display, aiming to discern their impact on consumer purchasing decisions. The study employed a causal research design, convenience-based convenience sampling method, and data collected through a structured questionnaire and used rigorous analysis, including correlation and multiple regression models. The findings revealed that design features, ambiance, brand image, and display significantly and positively influence consumer buying behavior, aligning with previous research on the importance of these elements in retail settings. However, a nuanced relationship emerged with product assortment, suggesting that an excessive variety may hinder buying decisions. This study contributes valuable insights for retailers seeking to refine their marketing strategies and create appealing shopping environments in the competitive world of superstores.